Original paperCD4+, CD8+ and CD4+CD25+ T lymphocytes in peripheral blood and peritoneal fluid of women with endometriosis - preliminary report - Górski, Jarosław; Szyłło, Krzysztof; Banasik, Małgorzata; Lewkowicz, Przemysław; Tchórzewski, Henryk (Archives of Medical Science, 2007)
Introduction: CD4+CD25+ cells play a major role in maintenance of immunological self-tolerance and negative control of pathological and physiological immunological reactions. Their absence or ill function leads to autoimmunization, immunopathology and allergy. The aim of this study was to investigate the prevalence of T lymphocyte subpopulations in peripheral blood and peritoneal fluid of women with endometriosis, as well as IL-10 generation by peripheral blood lymphocytes. Material and methods: The studied group comprised 24 women with endometriosis diagnosed during laparoscopy. The studied group was divided into two parts, depending on progression stage. The control group comprised 12 women without endometriosis. The percentages of subpopulations of T lymphocytes were evaluated via flow cytometry with IMK Plus test (BD Biosciences, USA). IL-10 concentration was analyzed by enzyme-linked immunosorbent assay – ELISA (R&D System, USA). Results: In the present study we observed higher percentage of CD4+CD25+ cells in peripheral blood of affected women in comparison with healthy subjects. We did not observe such a difference for the peritoneal fluid between the groups. Changes in number of CD4+CD25+ affect CD8+ shift. We observed a decreased amount of IL-10 in peripheral blood in women with endometriosis. The increase after PHA (phytohaemagglutinin) stimulation was lower in women suffering from endometriosis than in the control group. Conclusions: The quantitative disproportion of CD4+CD25+ T cells between peripheral blood and peritoneal fluid can affect the onset and development of endometriosis. The impaired migration and function of Treg cells alter composition of peritoneal fluid, which favours the onset and development of endometriosis.